Consecutive days of push start testing may mask the effect of starting style in skeleton - A pilot study. - Colyer, S. L.; Salo, A.; Bilzon, J.; Stokes, K. (University of Bath, 2012)
A fast start has been shown to be a prerequisite for success in skeleton (Zanoletti et al., 2006). However, there is a clear lack of knowledge regarding the optimum start technique. This is reflected in the wide range of starting styles adopted by athletes. Pre-season training, typically on dry-land push tracks, provides an opportunity to investigate different starting styles. In reality this often involves consecutive testing days, and thus fatigue may influence the results. The aim of this study was to investigate whether the effect of starting style on skeleton start performance could be detected over consecutive testing days.